Evaluation of mucoadhesive properties of native and modified starches of the root tubers of cocoyam (Xanthosoma sagittifolium) (2011)
The purpose of this study was to evaluate the bioadhesive properties of native and modified cocoyam (Xanthosoma sagittifolium) starches. The methods of modification were by pregelatinisation and acetylation. The starch particles were evaluated for characteristics like particle size, swelling ability, viscosity, and mucoadhesion. The mucoadhesive evaluation of the starches were done using the rotating cylinder methods in 0.1M HCl and Phosphate buffer (pH 6.8) to simulate the stomach and small intestine respectively. The mechanical properties of the compacted starches were determined using friability and crushing strength.The particles so prepared had irregular shape size ranged from 9.38 to 10.67mm. Mucoadhesion time was in the order Acetylated>Native>Pregelatinised starch in 0.1M HCl and Pregelatinised>Native>Acetylated starch in pH 6.8 Phosphate buffer. None of the severe signs such as appearance of epithelial necrosis, sloughing of epithelial cells were observed in ileum sections. The work concludes that modified cocoyam starches could be useful in targeted mucoadhesive drug delivery.